Discovering the fish fauna of a lagoon from the southeast of the Yucatan Peninsula, Mexico, using DNA barcodes - Adrian Emmanuel Uh-Navarrete; Martha Valdez-Moreno; Mariana E. Callejas-Jiménez; Lourdes Vásquez-Yeomans (PeerJ, 2023)
Background Aquatic ecosystems in the tropics are typically environments with a high species richness of fishes. These systems are also among the most vulnerable in the world, threatening the overall biodiversity of tropical regions. As a first step, it is important to enumerate the species in any ecosystem to promote its conservation. This study aims to inventory the ichthyofauna in the Chile Verde Lagoon, Quintana Roo, on the Yucatan Peninsula, a system fortunately well protected in Mexico, based on faunal surveys backed up with mtDNA barcodes. Methods We collected larvae, juveniles, and adults of fishes in the lagoon with a variety of sampling gear targeting various life stages. Species were identified using both morphology and DNA barcodes. The abundance of species and ichthyoplankton biomass (wet weight, suction technique) were calculated from 43 samples. Results We collected 197 adult and juvenile fishes and 3,722 larvae, of which 306 specimens were DNA-sequenced with a success rate of 96.7%. We identified 13 families, 24 genera, and 27 species in our inventory. The species number was estimated to comprise 75% of the potential total richness using the Chao 1 richness estimator. Clupeids and gobiids accounted for 87.9% of the total abundance of fishes, and, together with cyprinodontids, also accounted for the highest ichthyoplankton biomass. Conclusion Adult and juvenile fishes were identified by morphology and meristic values, however larvae required DNA barcoding to identify species. The high biomass and abundance of larvae of clupeids, gobiids and cyprinodontids suggests that the Chile Verde Lagoon may be important for reproduction of these species in the region. Microgobius microlepis, a marine goby species, is reported for the first time in an inland oligohaline system. This study provides a basis for future environmental assessment and biomonitoring of the Chile Verde Lagoon in the Yucatan Peninsula of Mexico.